Prospects for remodeling the hypertrophic heart with myosin modulators - Sewanan, Lorenzo R.; Shimada, Yuichi J. (Frontiers in Cardiovascular Medicine, 2022)
Hypertrophic cardiomyopathy (HCM) is a complex but relatively common genetic disease that usually arises from pathogenic variants that disrupt sarcomere function and lead to variable structural, hypertrophic, and fibrotic remodeling of the heart which result in substantial adverse clinical outcomes including arrhythmias, heart failure, and sudden cardiac death. HCM has had few effective treatments with the potential to ameliorate disease progression until the recent advent of inhibitory myosin modulators like mavacamten. Preclinical investigations and clinical trials utilizing this treatment targeted to this specific pathophysiological mechanism of sarcomere hypercontractility in HCM have confirmed that myosin modulators can alter disease expression and attenuate hypertrophic remodeling. Here, we summarize the state of hypertrophic remodeling and consider the arguments for and against salutary HCM disease modification using targeted myosin modulators. Further, we consider critical unanswered questions for future investigative and therapeutic avenues in HCM disease modification. We are at the precipice of a new era in understanding and treating HCM, with the potential to target agents toward modifying disease expression and natural history of this most common inherited disease of the heart.